2015
DOI: 10.1002/chem.201503650
|View full text |Cite
|
Sign up to set email alerts
|

1,1,1,3,3,3‐Hexafluoroisopropanol as a Remarkable Medium for Atroposelective Sulfoxide‐Directed Fujiwara–Moritani Reaction with Acrylates and Styrenes

Abstract: Axially chiral biaryls are ubiquitous structural motifs of biologically active molecules and privileged ligands for asymmetric catalysis. Their properties are due to their configurationally stable axis, and therefore, the control of their absolute configuration is essential. Efficient access to atropo-enantioenriched biaryl moieties through asymmetric direct C-H activation, by using enantiopure sulfoxide as both the directing group (DG) and chiral auxiliary, is reported. The stereoselective oxidative Heck reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 91 publications
1
44
0
4
Order By: Relevance
“…At the same time, a mild oxidant, AgOAc, is sufficient for the success of many Pd(OAc) 2 -catalyzed reactions, especially in CH 2 Cl 2 or DCE [97][98][99], passing through Pd(III) but not Pd(IV) intermediates, for which its strength is not enough [74,75,87,100,101].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, a mild oxidant, AgOAc, is sufficient for the success of many Pd(OAc) 2 -catalyzed reactions, especially in CH 2 Cl 2 or DCE [97][98][99], passing through Pd(III) but not Pd(IV) intermediates, for which its strength is not enough [74,75,87,100,101].…”
Section: Methodsmentioning
confidence: 99%
“…HFIP and its clusters are of considerable interest in catalysis [2,12,13] and solvation studies. [14][15][16][17] In the gas phase, HFIP exists in three OH torsional conformations: g', g,a nd the achiral t-form, which is the dominant species ( Figure 1) despite astatistical advantage of g. [18][19][20] In those studies,itwas demonstrated that the fraction of g conformers continuously decreases with cooling, going from nearly 0.5 at room temperature to essentially zero under free jet conditions, which is consistent with an energy penalty of about 5kJmol À1 . Fort he dimer, [20,21] the achiral tt-form was recently found to dominate.…”
mentioning
confidence: 99%
“…Owing to the importance of this structural motif, the catalytic atroposelective construction of axially chiral biaryls has been intensively investigated123456 and could be accessed by enantioselective oxidative/cross coupling of two aryl counterparts,78910111213 asymmetric construction of an aromatic ring14151617181920 and kinetic resolution/desymmetrization of biaryl compounds (Fig. 1a, left)21222324252627282930313233343536. However, in sharp contrast, the axially chiral styrenes bearing a chiral axis between a simple alkene and an aromatic ring have been rarely studied with respect to asymmetric synthesis and applications3738.…”
mentioning
confidence: 99%